1982
DOI: 10.1128/aac.22.6.1017
|View full text |Cite
|
Sign up to set email alerts
|

Comparative pharmacokinetics of aminoglycoside antibiotics in guinea pigs

Abstract: The pharmacokinetics of netilmicin, gentamicin, and tobramycin in plasma and in perilymph of guinea pigs were studied after a single intravenous Ototoxicity on both the vestibular and cochlear portions of the inner ear is a recognized side effect of aminoglycoside antibiotic therapy. It has been reported that the aminoglycoside antibiotics that are widely used in clinical practice, such as gentamicin, tobramycin, and amikacin, show similar perilymph drug concentrations (5) and provoke substantially overlappi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
2

Year Published

1983
1983
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 10 publications
1
7
2
Order By: Relevance
“…Furthermore, the perilymph/plasma ratio of all drugs remained well below 1, contradicting a possible accumulation in the inner-ear fluid for any of the drugs. These findings and their interpretation are in contrast to earlier pharmacokinetic studies of aminoglycosides which suggested a direct relationship between the severity of aminoglycoside ototoxicity and the levels of antibiotics reached in the perilymph (7,9,12,20,23). However, they are in agreement with recent studies (15,21,22) challenging such a hypothesis.…”
Section: Discussioncontrasting
confidence: 57%
“…Furthermore, the perilymph/plasma ratio of all drugs remained well below 1, contradicting a possible accumulation in the inner-ear fluid for any of the drugs. These findings and their interpretation are in contrast to earlier pharmacokinetic studies of aminoglycosides which suggested a direct relationship between the severity of aminoglycoside ototoxicity and the levels of antibiotics reached in the perilymph (7,9,12,20,23). However, they are in agreement with recent studies (15,21,22) challenging such a hypothesis.…”
Section: Discussioncontrasting
confidence: 57%
“…bolus injection of the four aminoglycosides tested appeared to produce the same pharmacokinetics, expressed by the beta half-life, distribution volume, and total body clearance (17). In guinea pigs, however, netilmicin has been shown to exhibit a greater volume of distribution in the central compartment and a greater total body clearance than gentamicin (7). Values of aminoglycoside binding to serum proteins ranging from 0 to 20% have been reported in humans and animals (19).…”
Section: Discussionmentioning
confidence: 99%
“…Many investigators believe that the inner ear damage is related to the concentration of AG in the perilymph (1,3,5,8,12,14). Although the rates of entry of AG into perilymph are much slower than those of AG into plasma, these drugs seem to accumulate in the perilymph after repetitive dosing because of their slow elimination rates from this body fluid.…”
mentioning
confidence: 99%
“…While trying to determine the kinetics of amikacin in perilymph, we wanted to reduce the number of animals required to establish the various rate constants. Since the perilymph compartment is both small and poorly accessible, generally only a single data point can be obtained from each animal (3,15). We recently modified a radioimmunoassay technique so that only 1 ,ul of perilymph sample is required (4).…”
mentioning
confidence: 99%